Pembuatan Floating Cage Berbahan PVC Sebagai Sarana Alternatif Usaha Mikro Budidaya Rumput Laut di Lingkungan Pattontongan Kabupaten Jeneponto - Wahyuddin Mustafa; Syamsul Asri; Farianto Fachruddin; Lukman Bochary; Ganding Sitepu; Rosmani -; Moh. Rizal Firmansyah; Hamzah -; A. Ardianti (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2020)
Generally, seaweed farmers on the Jeneponto coast, including the Pattontongan City seaweed farmer group, use the long line method instead of other seaweed cultivation methods. Alternative cultivation methods need to be introduced to increase their production capacity. One of the methods that can be offered to the farmers is the floating cage method. The development of the floating cage method by several researchers has revealed that seaweed's average growth rate is much better when compared with the long-line method. Initial attempts to introduce this method were carried out in the form of training by showing the shape or model of a floating cage and how to assemble it. Training is carried out online and offline. Online is used during material description while offline when the floating cage structure is assembled, launched, and anchored. The floating cage structure uses PVC as its material, while the adhesive bonding technique is used to connect the structural components. The floating cage model's characteristics have the dimensions of 2 x 2 x 0.5 meters, with a buoyancy of 0.13 m3, the structure weight of 43.18 kg, and the displacement of 134.23 kg. After attending this training, participants were able to (1) read the floating cage design, (2) mark (full scale) and cut the PVC pipe structure, (3) do the initial assembly and the final assembly in the form of splicing using adhesive bonding techniques, and (4) perform the process of launching and anchoring the floating cage structure. The skill of making their floating cage will save costs when they are about to apply the floating cage method instead of the long line method in their seaweed cultivation